ANALISIS SWOT DALAM PENGELOLAAN WAKAF PRODUKTIF BERBASIS BISNIS DI PONDOK PESANTREN DARUNNAJAH - Azka Islami; Efi Syarifuddin; Sulaiman Jajuli (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
In the midst of social and economic challenges faced by Indonesian society today, waqf institutions play a crucial and strategic role. Waqf, as a form of Islamic philanthropy, has significantly contributed to the development of mosques, schools, study circles, hospitals, orphanages, Islamic boarding schools, and other Islamic educational and social institutions. Waqf has two dimensions, serving as an act of worship towards Allah and a means of facilitating transactions among humans. One of the social functions of waqf is its ability to provide positive impacts on society at large when managed productively and optimally. Pondok Pesantren Darunnajah serves as an example of an educational institution that has successfully implemented productive and dynamic business-based waqf, adapting to the movements and conditions of human civilization. This study aims to analyze the management of productive business-based waqf in Pondok Pesantren Darunnajah through a SWOT analysis. A mix method approach is employed, utilizing SWOT analysis as a tool to identify factors that formulate institutional strategies. Data for this research was obtained through interviews and questionnaires administered to relevant parties in Pondok Pesantren Darunnajah. The findings indicate that the management of productive business-based waqf in Pondok Pesantren Darunnajah holds great potential and opportunities. The implementation of productive waqf falls within the growth-oriented strategy quadrant, allowing the utilization of existing strengths to seize various development opportunities in the future.